Adoption and use of internet banking in Zimbabwe: an exploratory study - Dube, Thulani; Chitura, Tofara; Runyowa, Langton (Journal of Internet Banking and Commerce, 2021)
This paper sought to explore the extent of adoption and usage of internet banking by commercial banks in Zimbabwe as well as investigate the challenges they face in the adoption of this technology. An exploratory research design was used to achieve the envisaged aims of the study. Overall, the results showed that while the majority of the banks in Zimbabwe have adopted internet banking, usage levels have remained relatively low, as not many customers are using this innovation in Zimbabwe. Regarding the challenges faced by banks in the adoption of IB, compatibility with existing legacy systems, cost of implementation and security concerns ranked high. The implications of the study are that banks in Zimbabwe should vigorously promote the usage of IB among customers while policy makers such as the Government and the Reserve Bank of Zimbabwe should increase investments targeted at infrastructure development so as to encourage banks and individuals alike to adopt the innovation.